2022
DOI: 10.1111/1744-7917.13151
|View full text |Cite
|
Sign up to set email alerts
|

The dynamic changes of genes revealed that persistently overexpressed genes drive the evolution of cyflumetofen resistance in Tetranychus cinnabarinus

Abstract: Changes in gene expression are associated with the evolution of pesticide resistance in arthropods. In this study, transcriptome sequencing was performed in 3 different resistance levels (low, L; medium, M; and high, H) of cyflumetofen-resistant strain (YN-CyR). A total of 1 685 genes, including 97 detoxification enzyme genes, were upregulated in all 3 stages, of which 192 genes, including 11 detoxification enzyme genes, showed a continuous increase in expression level with resistance development (L to H). RNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 72 publications
0
0
0
Order By: Relevance
“…7,52 In YN-CyR, transcriptome sequencing at different resistance levels revealed that the expression of P450, GST and CCE genes were all upregulated. 50 Interestingly, synergist assays suggest that the P450s are the key detoxification enzymes that mediate the formation of resistance to cyflumetofen in YN-CyR. 53 This is counter to the findings in CyR, and the reason for this difference in CyR and YN-CyR may be the different backgrounds of the initial strains (SS and YN-S, respectively).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…7,52 In YN-CyR, transcriptome sequencing at different resistance levels revealed that the expression of P450, GST and CCE genes were all upregulated. 50 Interestingly, synergist assays suggest that the P450s are the key detoxification enzymes that mediate the formation of resistance to cyflumetofen in YN-CyR. 53 This is counter to the findings in CyR, and the reason for this difference in CyR and YN-CyR may be the different backgrounds of the initial strains (SS and YN-S, respectively).…”
Section: Discussionmentioning
confidence: 95%
“…Our previous study demonstrated that CyR (selected from SS by cyflumetofen in the laboratory) and YN-CyR strains were both polygenic resistant. 49,50 In other words, the metabolic resistance to cyflumetofen is mediated by a variety of detoxification enzymes in T. cinnabarinus. For instance, the phase I detoxification enzyme CCEs most likely contribute to cyflumetofen resistance by suppressing the activation of cyflumetofen to its active metabolite, AB-1.…”
Section: Discussionmentioning
confidence: 99%